Improving China’s Global Lithium Resource Development Capacity - Li, Hanshi; Zhu, Ting; Chen, Xiangshun; Liu, Hanbin; He, Guangsheng (Frontiers in Environmental Science, 2022)
Flourishing sales of new electric vehicles have led to a considerable surge in demand for vital, upstream raw material, lithium (Li). As an essential energy metal and raw material for the production of batteries, lithium has become indispensable to electric vehicle industry. It has been identified as a strategic, emerging industrial mineral in China. Based on the imbalance between the supply and demand of lithium raw materials, this paper analyzes the current challenges of China’s lithium supply chain, especially mining and recycling, which will obstruct the realization of China's carbon neutrality. On this basis, relevant policy suggestions are proposed from three perspectives: strengthening lithium resource development and reserve capacity, promoting international cooperation for lithium supply, and properly regulating the circular economy of domestic lithium resources.